SOCIAL "TOP REVOLUTION" IN THE DAGESTAN AUL IN THE 20-30S' OF THE XX CENTURY: POLICY, IMPLEMENTATION, RESULTS - Iskenderov, G A (History, Archeology and Ethnography of the Caucasus, 2016)
The article deals with the problems of social and class structure of the village in the 20-30s of the 20th century, peculiarities of property inequality and social differentiation of the peasantry, main forms of social and economic relations and ties within the village, as well as between the village and national economic system as a whole. The author of thearticle analyzes rich factual material, mainly extracted from the state archive, published sources and historical literature of the recent years. Basing on the material, the author highlights key problems of collectivization of agriculture in the republic and makes an objective and comprehensive evaluation of these processes and phenomena.
Keywords: social; economy; class relations; class struggle; peasantry; kulaks; collectivization; structure; land issue; cooperation; tax; corn storage